Hidrólise extracelular de ATP e ADP pela enzima NTPDase1 em linfócitos de pacientes com leucemia linfocítica crônica-B - Zanin, Rafael Fernandes (2006)
The NTPDase1 enzymatic activity (E.C.3.6.1.5, Apyrase, ecto-ATP-diphosphohydrolase, CD39) which hydrolyses ATP and ADP, was analyzed in peripheral lymphocytes from patients with B chronic lymphocytic leukemia (B-CLL) which the main characteristic is the accumulation of monoclonal mature B-lymphocyte. The sample was composed by 23 patients with B-CLL whose were diagnosed according to the clinical and laboratorial criteria and also by the immunophenotypic characteristics. The patients were divided, according to the Binet staging system, in 4 groups: stage A (early), stage B (intermediate), stage C (advanced) and control group. The results demonstrated a significant increase in ATP hydrolysis (F(29,3)=26.79 p<0.001) for all the stages of the disease and related to the control as a function of length of disease advance with higher activity in stage C. ADP hydrolysis (F(29,3)=23.76 p<0.001) was also enhanced according to ATP results. Besides this it was found a great correlation between the activity of NTPDase-1 and the total absolute white cells count in peripheral blood. The alteration in NTPDase-1activity in lymphocytes from patients with B-CLL at the different stages, contributes to confirm the ectonucleotidases role in regulate the ATP and ADP levels, which actuates like signalling molecules in many blood cells like the lymphocytes. Therefore more studies need to be done so that we can elucidate such enzymatic system in the nucleotides and its role in the B-CLL.